2016
DOI: 10.1111/are.13191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of azithromycin on tilapia (Oreochromis niloticus): health status evaluation using biochemical, physiological and morphological biomarkers

Abstract: Bacterial diseases cause tilapia's high‐mortality outbreak. This study investigated the toxicity of azithromycin (AZT), a macrolide antibiotic that has been considered a possible therapeutic drug for tilapia aquacultural use. The 48‐h acute toxicity (50% lethal concentration, LC50; 48 h) of AZT was determined for Oreochromis niloticus. Thereafter, fish were exposed to 0, 1, 50 and 100 mg L−1 AZT during 14 days (chronic exposure) and measured the haematological variables, the activity of superoxide dismutase, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
(55 reference statements)
1
14
0
Order By: Relevance
“…A perusal of literature on the histopathological changes in the kidney of sh treated with various antibiotics at varied concentrations through different routes of administration indicated con icting results. For example, several earlier studies reported no changes in the kidney of sh (Fairgrieve et al 2005;Straus et al 2012;Shiogiri et al 2016); while others demonstrated histopathological alterations in the kidney (Reimschuessel and Ferguson 2006;Gaikowski et al 2013). Our observation on the progressive increase in the renal changes with the duration of treatment validated earlier studies (Reimschuessel and Ferguson 2006;Gaikowski et al 2013;Yang et al 2020;Limbu et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…A perusal of literature on the histopathological changes in the kidney of sh treated with various antibiotics at varied concentrations through different routes of administration indicated con icting results. For example, several earlier studies reported no changes in the kidney of sh (Fairgrieve et al 2005;Straus et al 2012;Shiogiri et al 2016); while others demonstrated histopathological alterations in the kidney (Reimschuessel and Ferguson 2006;Gaikowski et al 2013). Our observation on the progressive increase in the renal changes with the duration of treatment validated earlier studies (Reimschuessel and Ferguson 2006;Gaikowski et al 2013;Yang et al 2020;Limbu et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Epithelium lifting in gills, glycogen depletion in hepatocytes, and necrosis of endothelial cells in the renal corpuscles in fish ( Danio rerio ) exposed to diclofenac might be due to the interference of this drug with biochemical functions which indicate tissue damage 62 . Likewise, Azithromycin caused cellular deformation, lipid accumulation, and nuclear degeneration in fish ( Oreochromis niloticus ) 63 . The antibiotic drug tetracycline caused necrosis in the gill and liver tissues of Gambusia holbrook 64 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no alteration of the kidney tissues upon oral administration of OTC in Piaractus mesopotamicus (Carraschi et al, 2012) and azithromycin in O . niloticus (Shiogiri et al, 2016) were documented. A perusal of literature, as reviewed by Limbu et al (2020), also indicated conflicting results on the histopathological changes in the kidney of fish treated with various antibiotics at varied concentrations through different routes of administration.…”
Section: Figurementioning
confidence: 99%
“…Also, the intramuscularly administered OTC on Tinca tinca caused the tubular epithelial necrosis, which became severe in the haematopoietic renal tissue on day 7 (Soler et al, 1996). In contrast, no alteration of the kidney tissues upon oral administration of OTC in Piaractus mesopotamicus (Carraschi et al, 2012) and azithromycin in O. niloticus (Shiogiri et al, 2016) were documented. A perusal of literature, as reviewed by Limbu et al (2020), also indicated conflicting results…”
mentioning
confidence: 98%